PENGARUH KEGIATAN MONTASE TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK BESTARI KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI - Dity Elvika; Zulkifli '; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) To determine the fine motor skills of children before the implementation of activities montage. 2) To determine the fine motor skills of children after the implementation of activities montage. 3) To determine whether there is influence on the activity montage fine motor skills of children. 4) To determine the effect of activities against the montage of fine motor skills of children. This type of research used in this research is the experimental approach of a study that sought to influence specific variables other variables in strictly controlled conditions (Riduwan, 2005). The research sample is the child Class B consisting of 18 children, consisting of 8 men and 10 women. Collecting data using observation and documentation. Based on the survey results revealed that 1) the fine motor skills of children aged 5-6 years in kindergarten Bestari Cerenti Subdistrict Regency Kuantan Singingi before being given treatment through montage in the low category. This means that the need for the stimulus given to children to enhance fine motor development through montage. 2) fine motor skills of children aged 5-6 years in kindergarten Bestari Cerenti Subdistrict Regency Kuantan Singingi after being given treatment through montage activities have increased in the high category, meaning that there is a difference between the fine motor skills of children before and after being treated through montage. 3) Implementation of a montage of activities could affect fine motor skills of children aged 5-6 years in kindergarten Bestari Cerenti Subdistrict Regency Kuantan Singingi.Keywords: activity montage, fine motor